Modulation of antigen presentation by autoreactive B cell clones specific for GAD65 from a type I diabetic patient - BANGA, J P (Blackwell Science Inc, 2004)
We used a GAD65-specific human B–T cell line cognate system in vitro to investigate the modulation of GAD65 presentation by autoantibody, assessed in a proliferation assay. Generally, if the T cell determinant overlaps or resides within the antibody epitope, effects of presentation are blunted while if they are distant can lead to potent presentation. For three different autoreactive B–T cell line cognate pairs, the modulation of GAD65 presentation followed the mode of overlapping or distant epitopes with resultant potent or undetectable presentation. However, other cognate pairs elicited variability in this pattern of presentation. Notably, one B cell line, DPC, whose antibody epitope did not overlap with the T cell determinants, was consistently poor in presenting GAD65. Using the fluorescent dye Alexa Fluor 647 conjugated to GAD65 to study receptor-mediated antigen endocytosis showed that all the antigen-specific B cell clones were efficient in intracellular accumulation of the antigen. Additionally, multicolour immunofluorescence microscopy showed that the internalized GAD65/surface IgG complexes were rapidly targeted to a perinuclear compartment in all GAD-specific B cell clones. This analysis also demonstrated that HLA-DM expression was reduced strongly in DPC compared to the stimulatory B cell clones. Thus the capability of antigen-specific B cells to capture and present antigen to human T cell lines is dependent on the spatial relationship of B and T cell epitopes as well other factors which contribute to the efficiency of presentation.